Comparison of Concepts: The Nature of Education and the Purpose of Education - Hasnawi; Iskandar; Saifuddin; Zarkasyi (Journal Informatic, Education and Management (JIEM), 2026)
Education is a fundamental human need that plays a vital role in shaping the quality of individuals and the civilization of a nation. In the study of philosophy and educational science, discussions on the nature of education and its objectives occupy a central position because they serve as the conceptual basis for the implementation of education. The nature of education relates to the meaning, essence, and basic nature of education, while the objectives of education relate to the direction, results, and achievements to be achieved through the educational process. This article aims to examine in depth and compare the concepts of the nature of education and its objectives based on the views of experts, schools of educational philosophy, and Indonesian national education policy. The method used is a literature study with a descriptive-analytical and comparative approach. The results of the study indicate that the nature of education and its objectives are two interrelated and inseparable concepts. A comprehensive understanding of the nature of education is the main foundation in formulating educational objectives that are humanistic, contextual, and oriented towards the development of the whole person .